The Role of Applying the International Auditing Standard (620) To Benefit from The Work of An Expert in Improving Audit Quality: An Analytical Study of The Opinions of a Sample of Academics and Auditors in The Kurdistan Region – Iraq - Barzan Hasan Ahmed; Ghazi Othman Mahmod Noghariny (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The aim of this study is to clarify the role of applying the International Auditing Standard (620) to benefit from the work of an expert in improving audit quality.To achieve the goal of the study, the researcher relied on the primary sources, which is the design of the questionnaire that was designed based on previous studies and the theoretical framework for the study variables. The questionnaire consists of two main parts. The first part included the characteristics of the study sample, while the second part included (10) items for data collection and testing of hypotheses and answer the questions of the problem of the study.The study sample consist of (120) individual divided into, (40) university faculty, (50) certified auditors, and (30) chartered accountants in auditing offices and companies from Kurdistan Region .After the analysis of data and testing hypotheses, the researcher reached these following results:The application of the International Auditing Standard (620) to benefit from the work of an expert auditor has a direct and moral impact on improving the quality of the audit by improving the quality of the auditor’s final report, In light of the study results, the researcher recommended a number of recommendations, the most important is : Achieving the quality of auditing for offices and auditing companies is not achieved through what the auditors possess of skills and experience only, but rather these capabilities must be harnessed in applying the International Auditing Standard (620) and resorting to the opinions of experts and benefiting from their advice.